Perkembangan Desa Bandar Setia Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Ritonga, Syafruddin (Universitas Medan Area, 2015)
This study aims to determine (1) the development of land use, (2) growth in population and the development of rural infrastructure covering housing, transport, health, water supply, electricity, telecommunications in Desa Bandar Setia 2004-2009. This research is descriptive qualitative data collection techniques using observation and documentation. The population in this study are all Desa Bandar Setia region that includes the physical condition of the area, population, and infrastructure located at Desa Bandar Setia well as a sample. Data processing techniques performed through descriptive method qualitative comparative analysis of 2004-2009 Desa Bandar Setia systematically. The results showed that the development of land use for settlements grew 7 ha (1.94%), reduced wetland 6 ha (1.67%), dry land reduced by 2 ha (0.53%), highways incremented by 1 ha (0.28%); total population of 7,377 inhabitants experiencing growth or a growth rate of 11%; development of infrastructure for housing permanent and semi-permanent increase 849 units, housing non-permanent decreased 212 units, transport increased 772 units, health facilities especially clinic / dispensary increased 3 units, provision of safe water increased 827 units, customer electricity network increased 1,120 units (7.78%), and telecommunications increased 563 units.